Analisa Kritis Penggunaan Hipnoterapi dalam Konseling Pastoral - Nicko Hosea Layantara (Jurnal Missio Cristo, 2021)
Abstract: Pastoral counselling is an activity done by a pastor in giving advice, comforting, and strengthening the member of his/ her local church. One of the debateable topic that can or cannot be used in a pastoral counselling is hypnotherapy. Hypnotherapy is the application of hypnosis in healing the mental and physical problems (psychosomatic). This article explains whether hypnotherapy can be used or can’t be used in pastoral counselling and the reasons behind. The debates of the usage of hypnotherapy in a pastoral counselling can be solved by explaining hypnotherapy based on psychological concept and based on the Word of God. Based on psychological approach, hypnotherapy does not use a scientific method, because hypnotherapy cannot be tested empirically. In the other side, counselee cannot differentiate between the right memory and fantasy or suggested detail. Besides that, a counsellee cannot feel the attention, love, and empathy from the counsellor. In hypnotherapy, counsellee also has no power in rejecting things that are done by the counsellor, nor the suggestions given by the counsellor. Based on the Word of God, the unconsciousness, which is the basic theory of hypnotherapy is the veil of Sigmund Freud to hide his involvement with occultism, which is contrary to the Word of God. Hypnotherapy also cannot solve the root of human’s problem, which is sin. The problem solving of sin is only can be done by the consciousness from someone of his/ her sin and the need of salvation only in Jesus Christ. In the other part, hyonotherapy cannotbring counsellee to have a Christlikeness changing, because the changing of becoming Christlike is done by the Holy Spirit through the reading, contemplating, and applicating of God’s Word in counsellee’s life